PENGEMBANGAN PEMBELAJARAN STEAM BERBASIS KEARIFAN LOKAL MENENUN UNTUK MENINGKATKAN KEMAMPUAN MENCIPTA SISWA SD - Jouis Nieldy Otemusu; Helti Lygia Mampouw; Ferdy S. Rondonuwu (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to describe and analyze the application of Science, Technology, Engineering, Arts, and Mathematics (STEAM) learning assisted by ikat weaving in improving the creative abilities of fifth-grade students of SDN Sonraen, South Amarasi District, Kupang Regency, East Nusa Tenggara. The research method uses a descriptive qualitative approach with 32 students divided into eight heterogeneous groups. Data were collected through observation, assessment rubrics, interviews, questionnaires, and tests, then analyzed with the stages of data reduction, data presentation, and drawing conclusions according to the Miles & Huberman model. The results show that the application of STEAM learning assisted by ikat weaving can facilitate the active involvement of students in creative, collaborative, and problem-solving thinking processes through local culture-based activities. Students are able to produce simple woven works that combine aesthetic elements with the principles of science and technology. In addition, this activity improves students' creative abilities as seen from original ideas, problem-solving skills, and appreciation of local wisdom. Thus, culture-based STEAM learning is proven to be effective in fostering creativity while strengthening students' cultural identity. The conclusion of the research using the STEAM approach assisted by ikat weaving has proven effective in building students' creative abilities while making the learning process more contextual, enjoyable, and meaningful